2016
DOI: 10.1111/1471-0528.13864
|View full text |Cite
|
Sign up to set email alerts
|

The G‐spot: an observational MRI pilot study

Abstract: Objectives To identify a G-spot complex (GSC) in vivo in MRI examinations at 1.5 Tesla field strength.Design Observational study.Setting Single centre.Population Twenty-one consecutive patients (January-March 2014).Methods Imaging analysis of routine imaging protocols for usual medical indications with and without concomitant opacification of the vaginal cavity with inert ultrasound gel. The gel distends the otherwise collapsed vaginal walls, allowing for an improved discrimination of anatomic features. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…The same group overlooked data in the existing literature such as the histological description of a nerve ganglion, which was considered the histological landmark distinguishing the G‐spot from the vaginal and urethral walls (Ostrzenski et al, ). Additionally, they omitted information from the in vivo MRI study that revealed the G‐spot anatomical structure in 100% of cases when vaginal contrast was used (Maratos et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same group overlooked data in the existing literature such as the histological description of a nerve ganglion, which was considered the histological landmark distinguishing the G‐spot from the vaginal and urethral walls (Ostrzenski et al, ). Additionally, they omitted information from the in vivo MRI study that revealed the G‐spot anatomical structure in 100% of cases when vaginal contrast was used (Maratos et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The structural existence of the G‐spot was verified by postmortem anatomical studies, MRI investigation in vivo, and G‐spot histology (Ostrzenski et al, ; Ostrzenski, ; Maratos et al, ). Thabet () conducted an intraoperative anatomical study, and Hoag et al () performed a postmortem investigation.…”
Section: Introductionmentioning
confidence: 94%
“…stated ‘According to the description of Ostrzenski et al. The G‐spot was a neurovascular complex embedded within a fibroadipose tissue bed, in the anterior vaginal wall… To identify a G‐spot complex (GSC) in vivo in MRI examinations… MRI imaging data on the presumed anatomical location of the G‐spot is currently insufficient at best.’…”
Section: A Rebuttal: the G‐spot Does Not Existmentioning
confidence: 99%
“…The G‐spot is an erotically sensitive spot, its stimulation causes intense orgasms, therefore it is incomprehensible to study women, in vivo, without their sexual history and with no evidence of the so‐called ‘G‐spot’ orgasms, the conclusions of Maratos et al. concerning the ‘identification of G‐spot by MRI in 13/21 patients,’ have no scientific basis.…”
Section: A Rebuttal: the G‐spot Does Not Existmentioning
confidence: 99%
See 1 more Smart Citation